Pitch Walk and Savannah, Trinidad, B.W.I - (:unkn) unknown (My University, 2010)
This postcard features the electric tram car which ran alongside the Pitch Walk, between the sidewalk and the green grass of the Queen's Park Savannah.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Savannas--Trinidad and Tobago; Pitch Walk, The; Trolley cars--Trinidad and Tobago; Transportation--Trinidad and Tobago; [1930]; Trees--Trinidad and Tobago; Roads--Guard fences; Fences--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Sidewalks--Trinidad and Tobago; Pavements--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago; Queen's Park Savannah (Port of Spain)